An Application of Expert System to Identify Trees Utilizing Leaf Images - Muhammad lhsan Sarita; Sri Hartati (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2007)
AbstractTree identification is a very important to support almost all activities in the forest sector. Unfortunately, the inavailability of data and computer programs that is user friendly have caused ineficiency in tree identification. This research tries to make an expert system to identify trees by using the leaf images. To store the data in the knowledge base one must choose one of the some leaf images that are in the data base available in the program according the characteristic of the leaf. Each leaf image has a code and the accumulation of all codes build a tree code then this code is saved in the knowledge base. The tree code is used to identify a tree by making the comparison between input chosen by user and the tree code in the knowledge base using forward chaining. User who has information about a tree can add to the knowledge base but this information must be validated by an expert before it is used in the system. Another task of an expert is to give a CF (certainty factor) for each tree.The result of this research shows that no more errors are found due to input mistakes and the program is more user friendly. Another advantage is that the knowledge base is more flexible, dynamic and well organized Validation of knowledge base by experts can increase the quality and accuracy of using the knowledge base system.Keywords : expert system, leaf image, knowledge base, forward chaining, CF